Peningkatan Pembelajaran Materi Pengaruh Gaya Terhadap Benda Tema Daerah Tempat Tinggalku Melalui Model Inkuiri Terbimbing pada Peserta Didik Kelas IV SD N Kandangsapi 1 Sragen Tahun Ajaran 2020/2021 - Setyorini, Peni; Trisiana, Anita; Septonanto, Daniel Joko (RESEARCH FAIR UNISRI, 2021)
The objectives of this research are: (1) the application of the inquiry model to improve the learning of the material on the effect of style on the theme object of the area where I live in the fourth grade students of SD N Kandangsapi 1 Sragen; (2) improve the learning of the material on the effect of style on the theme of the area where I live in fourth grade students of SD N Kandangsapi 1 Sragen. Researchers in this study used classroom action research (CAR) which was divided into two cycles with two meetings in each cycle. The data used are qualitative and quantitative data. Data were collected by techniques in the form of tests, observations, interviews, and documentation. Data were analyzed using triangulation technique. Based on the research, it shows that guided inquiry can improve the learning of style influence material on the theme of the area where I live, as can be seen from the increase in the application of guided inquiry model observations to teachers starting from pre-cycle, cycle I II, namely 72.46% - 90.27%. The results of observations of pre-cycle students, cycles I, II were 61.80% - 85.88%. students complete for pre-cycle learning outcomes, the first and second cycles are 56.21% - 86.95%.